1991
DOI: 10.1029/91gb02586
|View full text |Cite
|
Sign up to set email alerts
|

Methane emission from rice fields as influenced by solar radiation, temperature, and straw incorporation

Abstract: Since rice fields emit methane, an important contributor to the increasing greenhouse effect, one of our goals is to characterize factors that influence this emission. To create a range in plant and soil temperature, solar radiation, and microbial substrate, rice fields were planted on April 13, May 18 and June 18 of 1990 on silty clay soils near Beaumont, Texas. Immediately prior to planting, one half of each field was supplemented with 6000 kg ha−1 of disc‐incorporated grass straw (Paspalum spp.). Methane em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
109
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(125 citation statements)
references
References 9 publications
14
109
1
1
Order By: Relevance
“…Averaged across sampling location, aboveground dry matter was greater from XL753 (2862 g m -2 ) than from CLXL729 and Roy J, which did not differ and averaged 2488 g m -2 , while aboveground dry matter measured from CLXL745 (2649 g m -2 ) did not differ from any of the other cultivars. Although previous studies have observed a positive correlation between CH 4 emissions and aboveground dry matter [52,62,70,71], data from this study did not support that relationship, where in this case the cultivar exhibiting greater CH 4 fluxes (Roy J) was one of the lowest accumulators of aboveground dry matter. Huang et al [71] suggested that the relationship between biomass accumulation and CH 4 emissions, although correlated when examining the relationship for a single cultivar, was not strong when evaluating the relationship among different cultivars.…”
Section: Aboveground Dry Matter and Grain Yieldcontrasting
confidence: 55%
See 1 more Smart Citation
“…Averaged across sampling location, aboveground dry matter was greater from XL753 (2862 g m -2 ) than from CLXL729 and Roy J, which did not differ and averaged 2488 g m -2 , while aboveground dry matter measured from CLXL745 (2649 g m -2 ) did not differ from any of the other cultivars. Although previous studies have observed a positive correlation between CH 4 emissions and aboveground dry matter [52,62,70,71], data from this study did not support that relationship, where in this case the cultivar exhibiting greater CH 4 fluxes (Roy J) was one of the lowest accumulators of aboveground dry matter. Huang et al [71] suggested that the relationship between biomass accumulation and CH 4 emissions, although correlated when examining the relationship for a single cultivar, was not strong when evaluating the relationship among different cultivars.…”
Section: Aboveground Dry Matter and Grain Yieldcontrasting
confidence: 55%
“…The seasonal pattern of CH 4 emissions increasing once the flood is applied, peaking near heading, then declining prior to flood release has been observed in numerous previous studies [30,32,49,51,53,59,60,61,62] and suggests that root exudates increase during vegetative growth providing substrate for methanogenesis and decrease again during grain fill as resources are translocated to the filling grains. Research conducted by Denier van der Gon et al [63] indicated that CH 4 emissions are related to allocation of photosynthetically derived C between roots and grains and that decreasing translocation of C to grains (i.e., removing florets prior to grain fill) causes an increase in C translocation to roots and an increase in CH 4 emissions.…”
mentioning
confidence: 88%
“…Because imperfect combustion effects of straw moisture were found only in relatively small straw stacks (5 or 10 kg), which resulted in a large amount of CO, CH 4 and NMVOC emissions, shredding and scattering rice straw on soils with combine harvesters may aggravate smoldering combustion to emit larger amount of GHGs. In addition, the straw shredding and scattering may also increase straw incorporation into paddy soils, further enhancing CH 4 emissions (Sass et al 1991). In future research, the quantification of CH 4 and N 2 O emissions from triple rice-cropping systems is required to fully assess the GHG emissions implications of different straw use.…”
Section: Discussionmentioning
confidence: 99%
“…Another crucial observation was that CH 4 emission increased significantly after 30 days of incubation. It has been reported [34,35] that there is a trade-off relationship between the CH 4 and N 2 O emissions in the soil. It can be observed from Fig.…”
Section: Ammonium Nitratementioning
confidence: 99%